Clinical Blood Examination As An Effort Of Secondary Prevention For Employees Of Grendel Factory With Diabetes And Hypertension In Malang - Indah Serinurani Effendi; Yosiene Dhea Elfira (Universitas Muhammadiyah Malang, 2025)
Background: Diabetes and Hypertension are the biggest contributors to the prevalence of chronic disease in Indonesia. The Data showed that Prevalence of Diabetes and Hypertension were increasing year by year. The most common cause of death in the world is cardiovascular disease which is closely related with diabetes and hypertension. Purpose : to find the early complication, comorbid and stop the disease progression by using chemical blood examination. The result hopefully can promote a health system for employees in Grendel Factory. Method : in well prepared condition, the blood was taken and examine the fasting glucose, lipid profile, urea, creatine serum, uric acid and albumin/creatinine ratio. Result : there were 30.7 % patients had elevated total cholesterol level, and 30.7% patients had elevated triglyceride level, 34.6% patients with elevated LDL-C level, two patients with microalbuminuria and one patients with significant macroalbuminuria.